Genetic dissection of the Mss4 locus mediating sex-biased cancer resistance in the rat peripheral nervous system - Berg, Linda van den; Kölsch, Bernd Ulrich; Winzen‐Reichert, Bettina; Fischer, Christine; Kutritz, Andrea; Kindler-Röhrborn, Andrea (International journal of cancer, 2015)
The incidence of neural tumors is sexually dimorphic in both, humans and rodents. The identification of genetic determinants contributing to sex-biased tumor development is an essential prerequisite for differential tumor prevention in males and females. F2 hybrids of inbred BDIV and BDIX rats, resistant and susceptible, respectively, to ethylnitrosourea-induced malignant peripheral nerve sheath tumors (MPNST) display a marked sex bias regarding tumor risk. Homozygous BDIV alleles at the Mss4 locus (90.9-111.2 Mb, chromosome 6) mediate MPNST resistance exclusively in female F2 rats according to a genome wide association analysis. This locus was functionally confirmed and fine mapped through MPNST induction in males and females of three congenic rat strains (BDIX.BDIV-Mss4a, b, d). As a consequence, it could be subdivided in Mss4.1 (98.8-99.7 Mb) mediating cancer resistance, and Mss4.2 (99.7-111.2 Mb) enhancing sex specificity. Positional candidate genes were selected through DNA sequencing and expression profiling using RNAs from trigeminal nerve tissue of parental and congenic male and female animals. The transregulatory fingerprint of BDIV or BDIX alleles at Mss4.1 and/or Mss4.2, respectively, provided insight into the processes influencing cancer risk in a sex-biased way. A group of genes, a fraction of which involved in Schwann cell differentiation, showed low, male-biased expression in nerve tissues under the control of BDIX susceptibility alleles, but high, female-biased transcript levels when controlled by BDIV resistance alleles at Mss4. The Esr2 gene located in Mss4.1 constitutes an interesting functional candidate together with a yet unidentified gene/enhancer in Mss4.2.
First published: 10 October 2014
Im Text ist Mss4 schräg gestellt
Gesehen am 07.07.2020